A heuristic based approach to vehicle routing model for Third Party Reverse Logistics provider. (11th May 2009) - Sasikumar, P.; Kannan, Govindan; Haq, A. Noorul
Recovery of used products is receiving much attention recently due to growing environmental concern. One of the main difficulties associated with product recovery activities is the degree of uncertainty in terms of timing and quantity of returned products. Thus, managing return flow requires a specialised infrastructure and relatively high handling cost and time. For that reason, demand for reverse logistics services from Third Party Reverse Logistics (3PRLs) providers is increasing. Vehicle routing plays a central role in logistics management. The aim of this study is to introduce a heuristic based approach for solving the Vehicle Routing Problem (VRP) of 3PRLs which can be described as the problem of designing optimal routes from one depot to a number of customers subject to constraints.